دراسة نقدية لعشرة أحاديث من الأحاديث المشهورة التي لم تثبت نسبتها إلى النبي = Critical study of ten popular ahadith related to the Prophet are not authenticated - Yaacob, Faridah; Mohammed Yaqub, Mohammed Abullais Shamsuddin (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia., 2018)
تناول البحث بالدراسة والتحليل لعشرة أحاديث من الأحاديث المشهورة بين الناس، وهي لم تثبت نسبتها إلى النبي . واعتمدت هذه الدراسة على المنهج الاستقرائي لجمع أقوال العلماء في درجات هذه الأحاديث. والمنهج التحليلي لتحليل تلك الأقوال. ومن أهم النتائج التي توصل البحث إليها: أنه ليس كل الأحاديث المشهورة ثابتة من النبي . ولا تجوز رواية الأحاديث المشهورة الموضوعة ولو كانت في فضائل الأعمال. واكتشف البحث عن بضعة طرق لعلاج انتشار الأحاديث الموضوعة في عوام الناس، منها: أن لا تذكر تلك الأحاديث الموضوعة، أو الأحاديث التي لا أصل لها في الكتب الدينية التي يقرؤها عامة الناس. وكذلك من الضروري لطلاب العلم أو العوام، الرجوع إلى العلماء أو المتخصصين في علم الحديث إذا لم يكن لديهم علم عن درجة الحديث الذي يريدون العمل به أم نشره بين الآخرين. ********************************************************* This study examines on ten popular fabricated Ahadith among the society. This study is using the inductive and analytical methods by explaining the opinions of Muslim scholars on those Ahadith. The study arrives at several findings, which the most important is; not all popular Hadith is from prophet peace be upon him. And the practice and transmission of fabricated Hadith is not permissible. The study attempts to suggest solutions in dealing with issue of practice and transmission of those fabricated Ahadith among the society such as do not mention any fabricated Ahadith in religion books which is read by public. It is also necessary for students of knowledge or common people who have no knowledge of the degree of the ahadith refer to scholars or expert in prophetic text if they want to practice or publish any hadith among others.